Vozes da Descolonização: narrativas de ex-alunos do centro de estudos superiores de Tefé da Universidade do Estado do Amazonas (CEST-UEA). - Lima, Felipe Ramos de (2018)
This work has as main proposal to analyze the dialogue between the Western knowledge declared officially by the University and the knowledge historically constructed from the narratives of alumnus of the CEST / UEA. The analysis was anchored from the tradition of postcolonial thought. The research adopted a methodological strategy that combined oral history and ethnography. As oral history, we favored the adoption of narratives from the life histories of CEST / UEA alumni, and in the ethnographic aspect we trained our eyes towards the "estrangement of the family" (VELHO, 1979). In this sense, the analysis of the narratives allow us to see productions that are being developed by the subjects of this research that has enabled the participation, the interaction and the production of a knowledge where different actors participate. We have also observed how this production of knowledge has emerged from different non-traditional spaces of knowledge and also from the problematic of the contexts in which they are situated. These reflections about knowledge as well as on the University in Tefé have been fundamental for the construction and contribution of an autonomous and decolonized knowledge.